A Single Distance Measuring Equipment (DME) Station‐Based Positioning System for Alternative Position Navigation and Timing (APNT). Issue 4 (December 2015) - Kim, O‐Jong; Kim, Chongwon; Song, Junesol; Lee, Taikjin; Park, Byungwoon; Kee, Changdon
Abstract: A single station‐based positioning system, known as Mosaic/DME, is introduced. This new system has been designed for the Alternative PNT (APNT) solution to air services as it acts as a backup navigation system in case of GNSS outage. The Mosaic/DME is a single station consisting of conventional DME and multiple pseudolites. The DME is operated using two‐way round signals for range measurements, with pseudolites broadcasting one‐way continuous signals for carrier phase measurements. The receiver in the aircraft receives both signals and calculates its own position after the ambiguity resolution process. In this paper, the feasibility of this system is studied via two topics: the performance of the navigation accuracy and ambiguity resolution using the weighted dilution of precision and Monte Carlo simulations. The results conclude that this system satisfies the required navigation accuracy of the APNT and yields a very fast and easy ambiguity resolution. Copyright © 2015 Institute of Navigation.